Testing the Efficiency of Indian Index Options Market by Employing the Box - Spread Strategy : Empirical Evidence from S&P CNX Nifty Index - Mutum, Kelvin; Das, Ashim Kr.; Singh, N. B.; Sarita Singha, U. (Indian Journal of Finance, 2018)
This article examined the efficiency of the Indian index options market by employing the box-spread arbitrage pricing relationship. The data collected for the study consisted of the daily closing prices of S&P CNX Nifty index options contracts from April 1, 2012 to March 31, 2017. The study demonstrated a frequent violation of box-spread parity. However, when the frequency and magnitude of the mispriced signals (violation of box-spread parity) were observed in light of specified liquidity and maturity levels, it was observed that most of the mispriced signals were concentrated at the illiquid levels and options which were going to get expired, and the magnitude of mispriced signals at the illiquid levels and options which were going to get expired were significantly larger than that of the liquid levels and options which were far away from the maturity date. Further, in order to verify whether the differences in the mean magnitude of the mispriced signals at different liquidity and maturity of the options contracts were statistically significant, the hypotheses were formulated and tested. The results of the study suggested that the Indian index options market during the period of study was efficient as most of the abnormal profits from the mispriced signals were not exploitable due to lack of liquidity.